2020
DOI: 10.1002/ecy.3060
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between Pacific salmon and aquatic and terrestrial ecosystems: implications for ecosystem‐based management

Abstract: Pacific salmon influence temperate terrestrial and freshwater ecosystems through the dispersal of marine‐derived nutrients and ecosystem engineering of stream beds when spawning. They also support large fisheries, particularly along the west coast of North America. We provide a comprehensive synthesis of relationships between the densities of Pacific salmon and terrestrial and aquatic ecosystems, summarize the direction, shape, and magnitude of these relationships, and identify possible ecosystem‐based managem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 59 publications
(106 reference statements)
3
34
0
Order By: Relevance
“…Our results indicate that there were diminishing returns for increasing egg abundance increasing egg consumption (i.e., type II functional response) for individual size classes of fish, but that higher egg numbers were needed to benefit diverse consumers. This aligns with the synthesis of Walsh et al (2020) who showed that ecological relationships between freshwater fish and salmon density tend to be asymptotic, and require extremely high salmon densities (7.3 kg/m 2 ) to reach 90% of their asymptote. Moore et al (2008) found that the relationship between salmon spawning density and the number of salmon eggs available for consumption is positively exponential and linked to nest superimposition by female salmon.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our results indicate that there were diminishing returns for increasing egg abundance increasing egg consumption (i.e., type II functional response) for individual size classes of fish, but that higher egg numbers were needed to benefit diverse consumers. This aligns with the synthesis of Walsh et al (2020) who showed that ecological relationships between freshwater fish and salmon density tend to be asymptotic, and require extremely high salmon densities (7.3 kg/m 2 ) to reach 90% of their asymptote. Moore et al (2008) found that the relationship between salmon spawning density and the number of salmon eggs available for consumption is positively exponential and linked to nest superimposition by female salmon.…”
Section: Discussionsupporting
confidence: 89%
“…Salmon‐bearing streams are a classic example of ecosystems that can experience resource pulses (Schindler et al 2003, Moore et al 2008, Walsh et al 2020). Salmon spawn and die in streams annually, producing carcass tissues and eggs that are consumed by a variety of predators and scavengers (Naiman et al 2002, Deacy et al 2016) such as stream fishes (Lang et al 2006, Bailey et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…For example, seabirds and anadromous fish bring marine‐derived nitrogen and phosphorus into terrestrial and freshwater ecosystems (e.g. Graham et al., 2018; Hood et al., 2019; Walsh et al., 2020), and the widespread collapse of seabird and anadromous fish populations has resulted in the global transfer of phosphorus from sea to land declining over 96% from historic levels (Doughty et al., 2016). Whereas the loss of historic connections among ecosystems disrupts nutrient cycles and recipient food web productivity (Gresh et al., 2000), the emergence of novel resource linkages among ecosystems that occur due to the establishment of non‐native species could be equally disruptive.…”
Section: Introductionmentioning
confidence: 99%
“…There is an urgent need to realign the scales of fisheries with biologically relevant scales (e.g., salmon populations or watersheds) to reduce conservation risks, create opportunities for sustainable harvest, and support salmon-dependent species and ecosystem processes (Healey 2009 , Ward et al 2009 , Gayeski et al 2018b , Freshwater et al 2020 , Walsh et al 2020 ). However, realignment of harvest toward greater terminal or in-river harvest will be of limited benefit if mixed-stock harvest rates remain high and fish are intercepted before reaching terminal fisheries, and terminal fisheries are not a panacea for sustainability if in-river fisheries overharvest returning salmon (Freshwater et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%